Employers’ Perspectives on Ohio’s Postsecondary Programs for Students with Intellectual and Developmental Disabilities - Diane Weinbrandt; Amy Shuman; Shannon Ott; Makenna Riter-Rowland; Eric Anderson; Andrew Buck; Jessie Green; Margo Izzo; Savannah Stark (Journal of Inclusive Postsecondary Education, 2023)
As postsecondary programs grow for students with intellectual and developmental disabilities (SwIDD), there is an increased focus on program evaluation and effectiveness, specifically related to impact on employment outcomes.  Ohio’s Statewide Consortium (OSC) of postsecondary programs for individuals with intellectual and developmental disabilities  interviewed seventeen current employer partners to determine to what degree they perceive OSC programs demonstrate quality indicators, as outlined in the eight Think College Standards for Inclusive Higher Education (TCSIHE).  Results indicate OSC programs are providing high-quality, positive work-based learning experiences for SwIDD and their employer partners that align to TCSIHE.  Key components of quality partnerships are highlighted as well as aspects of work-based learning experiences critical to skill development for SwIDD, and barriers to post-graduation employment outcomes.